An analysis of skills development in a transitional economy: the case of the South African labour market - Horwitz, Frank Martin (Taylor & Francis, 2013)
This article evaluates the extent to which both the supply and retention of scarce skills are adequate for South Africa to compete with similar emerging, transitional economies in the BRICS (Brazil, Russia, India and China) countries, a grouping it has recently joined. The aim of this article is to analyse the basis for skills shortages, policy measures taken and capacity to implement plans. Using a labour market approach to skills formation and integrating this with institutional analysis, this article critically evaluates the nature of the skills shortage, barriers to skills retention, HR strategies for talent management and public policy questions. This analysis concludes that South Africa is adversely affected by a shortage of intermediate and certain high-level skills. This analysis identifies four propositions for further investigation by policy-makers and researchers. The implications of this analysis underline the importance of appropriate labour market supply-side policy measures and firm-level HR strategic choices for skills retention and utilization.